Administration of Ascorbic Acid Alleviates Neuronal Damage After Cerebral Ischemia in ODS Rats - Naohiro Iwata; Naoto Ogawa; Tom Imai; Siti Sabirah Binti Ridzuan; Shinya Kamiuchi; Hirokazu Matsuzaki; Meiyan Xuan; Bo Yuan; Mari Okazaki; Yasuhide Hibino (Antioxidants)
Reactive oxygen species (ROS) contribute to cerebral damage in transient cerebral ischemia, making their elimination a key therapeutic target. Osteogenic disorder Shionogi (ODS) rats, which lack endogenous L-ascorbic acid (AA) synthesis, serve as a useful model for investigating AA’s protective effects against ischemic brain injury. ODS rats were given an AA-free diet (0% AA), 0.1% AA, or 1% AA in drinking water for two weeks before undergoing middle cerebral artery occlusion and reperfusion (MCAO/Re). The 0% AA group exhibited pronounced damage following MCAO/Re, characterized by the induction of lipid peroxidation, O2− production, inflammation-related gene expression, and extensive infarct formation. In contrast, the 1% AA group showed reductions in these markers, along with fewer TUNEL-positive cells and a smaller infarct volume. Notably, sodium-dependent vitamin C transporter 2 (SVCT2) expression increased in both two AA-supplemented groups, although the 0.1% AA group did not exhibit sufficient improvement in post-ischemic damage. A two-week intake of AA significantly alleviated MCAO/Re-mediated injuries associated with oxidative stress and inflammation in ODS rats. Sufficient AA intake is thus supposed to mitigate ischemic damage, possibly through SVCT2 upregulation and enhanced AA availability, leading to the suppression of oxidative stress and inflammation.